The Role of Junior High School Students in Group Discussions to Solve Fermi Problems - Mufidah, Wayan Indi Haidar; Susiswo, Susiswo; Irawati, Santi (Universitas Suryakancana, 2025)
This study investigates how junior high school students adopt and shift roles during group discussions while solving Fermi problems, using Positioning Theory as an analytical framework. The study employs a qualitative-descriptive approach with the subjects of eight students of class IX PD-CI MTsN 1 Kediri who were divided into two groups selected using purposive sampling techniques. Data were collected from audio and video recordings of group discussions, which were transcribed and coded for patterns of positioning, negotiation, and interaction, along with students’ written responses. The findings reveal that students take on different roles: novices often participate passively, facilitators organize the discussion and encourage participation, while experts contribute key information and guide reasoning. Some groups demonstrated dynamic role shifts throughout the activity, reflecting increased engagement and conceptual understanding, whereas others maintained more static participation patterns, limiting opportunities for collaborative idea exploration. This study uniquely analyzes role shifts among junior high school students through Positioning Theory in the context of Fermi problems. These findings highlight the importance of monitoring and structuring collaborative activities to promote equitable participation. For mathematics educators, understanding positioning patterns can inform instructional strategies, such as role rotation, supporting novice participation, and designing Fermi problems that foster active collaboration